Portrayal of Quarter Life Crisis through The Use of Satire in The Song Lyrics “24” by Sundial - Kartika, Dilah Ratna (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2022)
This study analyzed how a quarter-life crisis is portrayed through the use of satire in the song lyrics